Wind tunnel study on the pressure coefficient performance of different venturi shaped roof configurations for wind induced natural ventilation - Boroojerdian, Mohammad Mahdi; Adam, Nor Mariah; Mohd. Rafie, Azmin Shakrine (Trans Tech Publications, 2014)
Wind catchers are structures used for natural ventilation using wind induced into buildings. Recently this has attracted attention for green buolding features There is limited studies on the different venturi shapes and their effects on inducing wind into buildingss.. This study considered three configurations ie. the shallow ellipse, the ellipse and the hemisphere in a wind tunnel with different speeds ranging from 8 m/s to 20 m/s. The negative pressure coefficient at the lower center of the roof is considered as the criteria for higher ventilation rate. The shallow ellipse performed the best but due to construction limitations other alternatives are recommended.